MANAJEMEN PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH ISLAM - Burhanudin Burhanudin; Ari Prayoga; Irawan Irawan (stit-islamic-village, 2020)
This study aims to uncover the quality improvement planning, quality improvement control, quality improvement, and the results of improving the quality improvement of SMP Plus Al-Aqsa Sumedang. This study uses the Juran trilogy theory including; planning, controlling and improving the quality of education. The approach used in this research is qualitative with descriptive methods. Data collection techniques used include; observation, interview, and documentation study. The results of the study show that; first, the quality planning carried out at SMP Plus Al-Aqsa namely; the strategic step of analyzing market share needs, formulating the vision, mission, and goals of the institution. Second, quality control is implemented at SMP Plus Al-Aqsa namely; the determination of the work structure and supervision carried out by the principal and the internal quality team. Third, quality improvements carried out at Al-Aqsa Plus Junior High School namely; improvement of infrastructure to support institutional activities, formulate short-term, medium-term, long-term programs, and evaluate and identify specific areas that need improvement. The results of improving quality at SMP Plus Al-Aqsa have an impact on learning processes that are more innovative, student achievement and school achievement, customer satisfaction both internally and externally, and compliance with eight national education standards.